IDENTIFIKASI LEBAH KELULUT ASAL BANGKA DAN PENDATAAN JENIS TUMBUHAN PENGHASIL RESIN BAHAN BAKU PEMBUATAN PROPOLIS - Aghita Ade Novia Hirmarizqi; Eka Sari; Rosha Kurnia Fembriyanto; Nur Annis Hidayati; Rossy Hertati (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2019)
Resin is a substance needed by bees to produce a product, namely propolis. Resins are produced by plants as secondary metabolites. The diversity of plant species will affect the composition of active compounds in propolis. The more diverse types of plants will increase the quality of propolis. The purpose of this study was to identify the type of Kelulut bee and record and identify plants that were planted in bee culture, Pangkal Beras (West Bangka) and Lubuk Lingkuk (Central Bangka). Data collection on plant species is done by interview and exploration methods. The results of identification Kelulut bee in Pangkal Beras and Lubuk Lingkuk are Heterotrigona itama and Tetragonula fuscobalteata. There are ten types of resin-producing plants in both locations, namely Artocarpus integra Merr., Artocarpus heterophyllus Lam, Aquilaria malaccensis Benth., Cratoxylum glaucum Korth., Garcinia atroviridis Griff. ex T.Anderson, Hevea brasiliensis (Willd. ex A.Juss.) Müll. Arg., Macaranga triloba Müll. Arg., Mangifera odorata Griff., Mangifera indica Thwaites, and Spondias pinnata (L.f.) Kurz.